Longitudinal changes in Mediterranean diet adherence and perceived benefits and barriers to its consumption in US university students - Yildiz, Serhat; Downing, Patrick; Knight, Caroline J.; Frugé, Andrew D.; Greene, Michael W. (Frontiers in Nutrition, 2024)
The Dietary Guidelines for Americans has recommended consumption of a Mediterranean diet (MD) for overall health and well-being, and the US News & World Report has ranked the MD as the top diet overall for the past six consecutive years. However, it is uncertain if university students in the United States (US) have increased their adoption of this dietary approach over these past six years.Longitudinal cross-sectional survey conducted in three cohorts (2018, 2020, 2022) utilizing regression models to assess MD Adherence and other relevant outcomes variables.Setting: University in the southern US.Participants: Students (n=761) enrolled in undergraduate introductory nutrition course.Results: Survey respondents were 83% female, 91% white, and 97% ages 18-24. Predictors of MD adherence were older age, female gender, and health-related qualifications. MD adherence was lowest in 2022. The 2022 group perceived less MD health benefits, weight loss, ethical concerns, natural content, and sensory appeal compared to the 2018 group. During the COVID-19 pandemic, changes in eating behavior were examined in the 2020 and 2022 groups. We observed that participants in the 2022 group had a greater frequency of snacking and a lower frequency of eating out compared to 2020 group. Conclusions: MD adherence did not increase over time in US university students. These findings underscore the need for targeted interventions and education to promote healthier eating habits in university students. 2022 -3.78 0.23 < 0.001 -3.7 0.24 < 0.001 ‡ Number of questions in each factor * p values < 0.05 from are indicated in bold font † Crude linear model † † Adjusted linear model for sex, age, ethnicity, education, and BMI ∇ 2018 was used as the reference (Ref) group in the linear model